The use of digital technology platforms in the context of cybersecurity in the industrial sector - Krzysztof Bartczak (Foundations of Management, 2021)
This study discusses the use of digital technology platforms (DTPs) in the context of cyber-security in the industrial sector, with a focus on digital industry (industrial) platforms (DIPs). A definition of DTPs is presented, including the author's interpretation, as well as the scope of DTP application in the industrial sector, which includes, in particular, European Digital Platforms (EDPs) and Polish Digital Platforms (PDPs), such as non-ferrous metals PDP or intelligent transport systems PDP. This is followed by a section covering the theoretical basis of the study that highlights the key challenges and risks associated with the use of DTPs as well as the methods for their neutralization in the form of specific concepts and systems that can be employed in the industrial sector. The subsequent section of the study is based on results of the author's own survey which collected information from a total of 120 companies operating in Poland, which were granted subsidies under the Operational Program Innovative Economy for investments involving the implementation and development of DTPs. The survey was carried out using a questionnaire developed by the author, which consisted of 23 questions. In this respect, as shown by the author's own studies, of greatest relevance are hardware failures and Internet outage events. Most importantly, concerns about such risks are some of the major factors underlying the negative attitudes of management staff of industrial companies toward DTPs, and therefore, it is so important to ensure that any such risks can be effectively addressed. They can be avoided through the use of certain concepts and systems such as STOE or CVSS. A typical company may know the model of DTPs in the context of challenges in the field of cybersecurity through this study; in particular, it can improve IT security.
Keywords: M11; M15; D20; 650; platform economy; digital technology platforms; cybersecurity; risks; industrial sector